On the Partial Public Provision of a Private Good - Rajshri Jayaraman (Center for Economic Studies and ifo Institute (CESifo), 2002)
When the public provision of private goods is partial rather than universal, public supply may be supplemented by the entry of private firms in the market for the private good. The main purpose of this paper is to explore whether partial public provision helps or hinders aggregate access to the private good by exploring the effect of public provision on that of private firms. We find that the outcome depends on such things as the targeting of public provision, market structure, and the level of public provision.
Keywords: 330